THE USAGE OF NEARPOD AND MENTIMETER IN ENHANCING WRITING ABILITIES OF EFL LEARNERS - Rajapova, Ruzigul (Educational Research in Universal Sciences, 2023)
Writing is so a vital skill that every ESL learner should acquire. Because it plays a major role in documentation and written communication. So governments in every country pay a particular attention to enhance writing skills in ESL in order to develop many important fields such as economy, medicine and etc. On the grounds that good writing skill can help to improve such fields increasingly to sign vital contracts between our country’s companies and foreign ones. However, some mentors consider teaching writing efficiently as an intricate process for them owing to some reasons. They know that being a good writer in ESL requires a lot of knowledge, critical thinking and creativity. It should be admitted that being proficient in Grammar does not mean advanced writing proficiency. Uptill now, grammar translation, direct method, communicative language teaching have been used as the most beneficial methods for teaching writing. Nevertheless, these methods can not be met demands of digital learners who are such kinds of learners who prefer gaining knowledge on any science or any language in a digital way, namely with advanced online technologies. That’s why, several linguists suggest using Nearpod and Mentimeter in teaching writing process.